(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Gestational anemia is a global health concern. The initial 20 weeks of pregnancy are critical for the development and prevention of negative pregnancy outcomes related to low hemoglobin levels. Objective: To compare the structural characteristics of the umbilical cord (UC) in women diagnosed with anemia in the first 20 weeks of pregnancy with those without anemia. Methods: This was a retrospective cohort study conducted at the Kenyatta National Hospital. Thirty-six umbilical cords were collected and examined for differences in gross and histological features. Comparisons were also made between the fetal and placental ends of the UC for these features. Results: Significant differences were observed in the diameter of the umbilical cord, the volume of Wharton’s jelly, and the intima-media thickness of the umbilical vein (all p<.05) between the anemic and nonanemic group. Disruption of the internal elastic lamina and intimal thickening of the umbilical vein were more prominent toward the fetal end of the UC in the anemia group. However, the increased risk of low birth weight in this group was not statistically significant, with a relative risk (RR) of 4.0 (95% CI: 0.49-32.39). Conclusion: Anemia within the first 20 weeks is associated with structural changes in the UC that may contribute to adverse outcomes. Improving hemoglobin levels before conception and during early pregnancy is therefore critical. Keywords: adverse pregnancy outcomes, anemia, gestational anemia, low birth weight, umbilical cord.